I am a Driver-Partner. (1st December 2017) - Luke Munn
Abstract : What does it mean to be a worker in the sharing economy? How is this subjectivity produced by the algorithmic performativities infused into these platforms and how, in turn, is this subjectivity negotiated with? To investigate this question, this article examines the particular algorithmic system of Uber, a labour platform which connects passengers with self-employed 'Driver-Partners'. Using the notion of the machine, it explores the intentions and agencies embedded in two strategic intersections of matter. The Partner-Management-Messaging machine attempts to shape the behaviour of the Driver-Partner through an array of messaging and motivational techniques. The Driver-Partner responds ambivalently through strategies which both collaborate and conflict with these operational logics. The ViolentFlesh-Passenger machine delves into the informatic notion of the body which Uber maintains and the concrete processes that constantly reinforce this notion. However, this informatic identity fails to fully exhaust the possibilities of the corporeal, highlighting the disparity between this ostensibly ethereal and largely vestigial driver and the violent actions nevertheless carried out by bodies on other bodies. These cases exemplify the negotiations and contingencies which are ever present within algorithmically regulated systems of labour.